Use of antidepressant medication after road traffic injury. Issue 7 (July 2015) - Berecki-Gisolf, Janneke; Collie, Alex; Hassani-Mahmooei, Behrooz; McClure, Roderick
Abstract Objectives Mental ill health after road traffic injury is common, as is the use of antidepressant medication after injury. Little is known about antidepressant use by injured people prior to their injury. The aim of this study is to describe the nature and extent of antidepressant use before and after road traffic injury. Methods Victorian residents who claimed Transport Accident Commission (TAC) compensation for a non-catastrophic injury that occurred between 2010 and 2012 and provided consent for Pharmaceutical Benefits Scheme (PBS) linkage were included (n = 734). PBS records dating from 12 months prior through to 12 months post injury were provided by the Department of Human Services (Canberra). PBS and TAC claims data were linked. Results Among participants, 12% used antidepressants before injury (84.4 Defined Daily Doses/1000 person-days) and 17% used antidepressants after injury (114.1 DDD/1000 p-d). Only 7.7% of the injured cohort commenced antidepressant treatment post injury. Thus, of all post-injury antidepressant use, 45% could potentially be related to the incident injury, with the remaining 55% most probably a continuation of pre-injury use. Pre-injury use was more common among women (109.4 vs. 54.6 DDD/1000 p-d, p < 0.0001), and those with whiplash injury (119.3 vs. 73.1, p = 0.03). Cyclists and motorcyclists were less likely to use antidepressants pre-injury than car drivers (18.3 vs. 16.9 vs. 109.3, respectively; p < 0.001). Conclusions Less than half of post-injury antidepressant use could potentially be attributable to the incident injury. These results highlight the importance of obtaining information on pre-injury health status before interpreting post-injury health service use to be an outcome of the injury in question.